2019
DOI: 10.3382/ps/pez548
|View full text |Cite
|
Sign up to set email alerts
|

A novel recombinant avian leukosis virus isolated from gamecocks induced pathogenicity in Three-Yellow chickens: a potential infection source of avian leukosis virus to the commercial chickens

Abstract: One natural recombinant avian leukosis virus (ALV) strain GX14DJ3–18 was isolated from a native gamecock by DF-1 cell culture and identified with Polymerase Chain Reaction (PCR), immunofluorescence assay and the viral genome's nucleotide sequencing. This strain was revealed as a novel recombinant virus with nucleotide sequence similarities of 95.4% Long Terminal Repeated (LTR), 95.8% 5′, UTR, 97.9% gag, and 92.9% 3′untranslated regions (UTR) in ALV-J. Also we found sequence similarities of 99.3% pol and 99.0% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 19 publications
2
13
0
Order By: Relevance
“…Furthermore, the analysis showed that pol and gag genes were highly conservative, and the homology of different strains was all higher than 95.0%. The env gene of GXRJ01 shares 96.8% identity with NX0101 (ALV‐J) but around 58% identities with strains in other subgroups, while the LTR of GXRJ01 shares the highest identity with EV‐1 (94.7%, ALV‐E), demonstrating that it is a natural recombinant virus, which has the same recombination pattern as the previous strains (Barbosa et al., 2008; Wang et al., 2017, 2019), that is, the LTR region is replaced by counterparts of other subgroups.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Furthermore, the analysis showed that pol and gag genes were highly conservative, and the homology of different strains was all higher than 95.0%. The env gene of GXRJ01 shares 96.8% identity with NX0101 (ALV‐J) but around 58% identities with strains in other subgroups, while the LTR of GXRJ01 shares the highest identity with EV‐1 (94.7%, ALV‐E), demonstrating that it is a natural recombinant virus, which has the same recombination pattern as the previous strains (Barbosa et al., 2008; Wang et al., 2017, 2019), that is, the LTR region is replaced by counterparts of other subgroups.…”
Section: Resultsmentioning
confidence: 92%
“…But beyond that, the genomic variability of ALV is also shown as gene recombination, which refers to the integration of gene fragments from different ALVs in the process of reverse transcription during mixed infection, thus forming natural recombinant strains (Cai et al., 2013; Lin et al., 2017; Wu et al., 2010; Zhao, Rao, Liao, & Cao, 2018). Most of the recombination events occurred in A, B, E and newly identified K subgroups, while the main form was the replacement of long‐terminal‐repeat (LTR) region (Barbosa, Zavala, & Cheng, 2008; Wang, Yang, Lin, Li, & Wei, 2017; Wang et al., 2019). Several analyses revealed that ALV‐J is also easy to be recombined, while most of the recombinant events appeared in the env gene with no report mentioning that the coding region ( gag‐pol‐env ) of ALV‐J is recombined with the LTR of other subgroups (Liang et al., 2019; Lin et al., 2017; Wu et al., 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After 3 blind passages in DF-1 cells, the viruses were respectively confirmed by indirect immunofluorescence assay using subgroup specific monoclonal antibody JE-9 ( Wang et al., 2019 ). The culture supernatants of the third passage of each sample were harvested for the detection of ALV group-specific antigen p27 with the enzyme-linked immunosorbent assay kit (IDEXX, Westbrook, ME).…”
Section: Methodsmentioning
confidence: 99%
“…Avian leukosis virus belongs to the genus Alpharetroviru s and the family Retroviridae ( Wang et al., 2019 ). The proviral DNA arrangement of the genome of ALV was 5′LTR-leader- gag - pol - env -3′LTR and the full-length of the genome sequences of ALV was 7,200 bp-7,800 bp ( Wang et al., 2018a ).…”
Section: Introductionmentioning
confidence: 99%